Benchmarking electrical engineering diploma laboratory syllabus (Industrial Electronics) with MLVK noss - Abdullah, Morina; Mohd. Noor, Norliza (Universiti Teknologi Malaysia, 2006)
Beside having graduating with a Diploma , most students will find having a certificate from MLVK is an asset for them to find a better paying job. MLVK certificate is an acknowledgement for technical people acquiring mtoor skills according to difficulty level. The current scenario, the student on their effort has to go to MLVK testing center and undergo the whole programme design by MLVK before getting the certificate. MLVK NOSS Level 1 test based on fundamental skills of using and handling electrical/ electronics apparutus such as an oscilloscope and measuring meters. MLVK NOSS Level 2 test competency students on constructing and troubleshooting electrical circuitry using common electronics devices sucah as transistor, diode and op-amp. Whereby MLVK NOSS Level 3 test the competency on constructing and troubleshooting electrical circuitry using advance devices such as SCR and IC. Level 3 also stress on supervisory skills and reading and use manual effectively. Electrical Engineering Diploma Laboratory course covers a wide are which include constructing and troubleshooting , design and testing electronics circuitry that emphasis on motor skills of the students. MLVK NOSS only cover construction and troubleshooting of electronics circuitry. This is a novel research where there is no existing studey on equating motor skills acquired by the students of Electrical Engineering Diploma students wtih MLVK NOSS. The ultimate aim of this research is to obtain endorsement from MLVK to grant an automatic certificate to the Electrical Engineering Diploma students according to their academic year.